Photoluminescence imaging of solitary dopant sites in covalently doped single-wall carbon nanotubes. Issue 48 (20th November 2015) - Hartmann, Nicolai F.; Yalcin, Sibel Ebru; Adamska, Lyudmyla; Hároz, Erik H.; Ma, Xuedan; Tretiak, Sergei; Htoon, Han; Doorn, Stephen K.
Abstract : Correlated 2-color photoluminescence imaging of covalently doped carbon nanotubes demonstrates exciton localization following diffusive transport to dopant sites. Abstract : Covalent dopants in semiconducting single wall carbon nanotubes (SWCNTs) are becoming important as routes for introducing new photoluminescent emitting states with potential for enhanced quantum yields, new functionality, and as species capable of near-IR room-temperature single photon emission. The origin and behavior of the dopant-induced emission is thus important to understand as a key requirement for successful room-T photonics and optoelectronics applications. Here, we use direct correlated two-color photoluminescence imaging to probe how the interplay between the SWCNT bright E 11 exciton and solitary dopant sites yields the dopant-induced emission for three different dopant species: oxygen, 4-methoxybenzene, and 4-bromobenzene. We introduce a route to control dopant functionalization to a low level as a means for introducing spatially well-separated solitary dopant sites. Resolution of emission from solitary dopant sites and correlation to their impact on E 11 emission allows confirmation of dopants as trapping sites for localization of E 11 excitons following their diffusive transport to the dopant site. Imaging of the dopant emission also reveals photoluminescence intermittency (blinking), with blinking dynamics being dependent on the specific dopant. Density functional theory calculations were performed to evaluate the stability of dopants and delineate the possible mechanisms of blinking. Theoretical modeling suggests that the trapping of free charges in the potential well created by permanent dipoles introduced by dopant atoms/groups is likely responsible for the blinking, with the strongest effects being predicted and observed for oxygen-doped SWCNTs.